2019
DOI: 10.7150/jca.34506
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Resveratrol-Arsenic Trioxide Combination Treatment Synergistically Induces Apoptosis of Adriamycin-Selected Drug-Resistant Leukemia K562 Cells

Abstract: Leukemia cells can develop resistance to apoptosis induced by chemotherapeutic agents. Concomitant multidrug resistance of cells remains the greatest clinical obstacle in the effective treatment of blood and solid tumors. Natural products have been identified that possess the capacity to modulate chemotherapeutic resistance and induce apopotosis. In this study, we generated adriamycin-resistant K562 leukemia (K562/RA) cells and compared the responses of sensitive and resistant leukemia cells to the natural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…[19] Recent studies suggest that combinations of ROS-generating anticancer agents are useful for the therapy of acute myeloid leukaemia because of the synergic effects of their anti-leukaemia activities. [31,32] Our study showed that citbismine-E acts as a ROS-generating anticancer agent in human myeloid HL-60 cells. The combination of citbismine-E with other anti-leukaemia agents might be a better strategy for enhancing the anticancer activity of citbismine-E.…”
Section: Resultsmentioning
confidence: 78%
“…[19] Recent studies suggest that combinations of ROS-generating anticancer agents are useful for the therapy of acute myeloid leukaemia because of the synergic effects of their anti-leukaemia activities. [31,32] Our study showed that citbismine-E acts as a ROS-generating anticancer agent in human myeloid HL-60 cells. The combination of citbismine-E with other anti-leukaemia agents might be a better strategy for enhancing the anticancer activity of citbismine-E.…”
Section: Resultsmentioning
confidence: 78%
“…RSV has been shown to aid the apoptosis of human BC cells without harming healthy cells [18,27,28]. In the current study, RSV had a synergistic inhibitory effect with ATO on MCF-7 cells, but also potentially diminished the toxicity of ATO [20,22]. In the present study, ATO (0-16 μM) alone or combined with RSV (0-100 μM) was used.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, RSV was shown to be safe in healthy volunteers in one clinical trial [19]. Furthermore, RSV has been found to inhibit the proliferation and promote the apoptosis of tumor cells induced by ATO and protect healthy cells against the toxicity wrought by ATO [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…ATO has recently been used widely for the treatment of hematologic tumors and a variety of solid tumors, with good results [26,27,37,38]. Numerous studies have demonstrated that ATO induces apoptosis in tumor cells, often accompanied by autophagy [39].…”
Section: Discussionmentioning
confidence: 99%